Mefloquine induces ER stress and apoptosis in BRAFi‐resistant A375‐BRAFV600E/NRASQ61K malignant melanoma cells targeting intracranial tumors in a bioluminescent murine model. Issue 6 (13th April 2022) - Jandova, Jana; Park, Sophia L.; Corenblum, Mandi J.; Madhavan, Lalitha; Snell, Jeremy A.; Rounds, Liliana; Wondrak, Georg T.
Abstract: Molecularly targeted therapeutics have revolutionized the treatment of BRAF V600E ‐driven malignant melanoma, but the rapid development of resistance to BRAF kinase inhibitors (BRAFi) presents a significant obstacle. The use of clinical antimalarials for the investigational treatment of malignant melanoma has shown only moderate promise, attributed mostly to inhibition of lysosomal‐autophagic adaptations of cancer cells, but identification of specific antimalarials displaying single‐agent antimelanoma activity has remained elusive. Here, we have screened a focused library of clinically used artemisinin‐combination therapeutic (ACT) antimalarials for the apoptotic elimination of cultured malignant melanoma cell lines, also examining feasibility of overcoming BRAFi‐resistance comparing isogenic melanoma cells that differ only by NRAS mutational status (BRAFi‐sensitive A375‐BRAF V600E /NRAS Q61 vs. BRAFi‐resistant A375‐BRAF V600E /NRAS Q61K ). Among ACT antimalarials tested, mefloquine (MQ) was the only apoptogenic agent causing melanoma cell death at low micromolar concentrations. Comparative gene expression‐array analysis (A375‐BRAF V600E /NRAS Q61 vs. A375‐BRAF V600E /NRAS Q61K ) revealed that MQ is a dual inducer of endoplasmic reticulum (ER) and redox stress responses that precede MQ‐induced loss of viability. ER‐tracker TM DPX fluorescence imaging and electron microscopy indicated ER swelling, accompanied by rapid induction of ER stress signaling (phospho‐eIF2α, XBP‐1s, ATF4). Fluo‐4 AM‐fluorescence indicated the occurrence of cytosolic calcium overload observable within seconds of MQ exposure. In a bioluminescent murine model employing intracranial injection of A375‐Luc2 (BRAF V600E /NRAS Q61K ) cells, an oral MQ regimen efficiently antagonized brain tumor growth. Taken together, these data suggest that the clinical antimalarial MQ may be a valid candidate for drug repurposing aiming at chemotherapeutic elimination of malignant melanoma cells, even if metastasized to the brain and BRAFi‐resistant.